Pemberdayaan Masyarakat dalam Pengelolaan Sampah melalui Pembuatan Pembakaran Sampah Minim Asap (Rocket Stove) di Dusun Allukeke - Dian Rezki Wijaya; Syahrul Basri; M. Fais Satrianegara; Zulqadri Zulqadri; Ainun Nardiah (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
Open burning of household waste remains the dominant waste disposal practice in rural areas of Indonesia, posing significant risks to public health and environmental quality. This community service activity aimed to provide an innovative, low-smoke waste combustion solution — the rocket stove incinerator — to the residents of Dusun Allukeke, Desa Belapunranga, Kecamatan Parangloe, Kabupaten Gowa. A baseline survey conducted during PBL 1 revealed that 87.6% of households disposed of waste through open burning. An asset-based community development (ABCD) approach was adopted, engaging community members at every stage from planning, construction, to utilisation. The rocket stove was constructed over three days using locally available materials and was demonstrated to significantly reduce visible smoke emissions compared to conventional open burning. The technology works through a vertically insulated combustion chamber that promotes near-complete combustion, reducing waste volume by 50–90% while suppressing particulate matter and hydrocarbon emissions. Community participation strengthened local ownership of the solution. This activity demonstrates that appropriate technology co-constructed with communities can serve as a practical, sustainable, and replicable model for rural waste management.